Transient neuromotor phenotype in transgenic spastic mice expressing low levels of glycine receptor β‐subunit: an animal model of startle disease - Becker, Lore; Hartenstein, Bettina; Schenkel, Johannes; Kuhse, Jochen; Betz, Heinrich; Weiher, Hans (European journal of neuroscience, 2000)
Startle disease or hereditary hyperekplexia has been shown to result from mutations in the α1‐subunit gene of the inhibitory glycine receptor (GlyR). In hyperekplexia patients, neuromotor symptoms ge...
Published: 09 October 2008
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 10.05.2021